(untitled) (American Journal of Islam and Society, 1992)
The Fiqh Council of North America discussed a variety of issues at this meeting. To promote jointly prepared and considered legal opinions (fatawa), the council welcomes the input of Muslim social scientists on the following issues: 1. A lunar calendar for North America. Its policy is to a) provide interested parties with detailed astronomical projections for the next seven to ten years; b) provide information on the Sharl’ah’s perspective vis-avis astronomical calculations; c) urge Muslims to observe the moon regularly and report their sightings; and d) allow each community to decide whether it will use the information as a guide to physical sighting or as a definitive table for the beginning and end of the lunar months. 2. Whether women may share in the management and administration of mosques, Islamic schools, and executive councils of Islamic organizations (youth and studemt organizations in particular). It was noted that there is no legal reason to prevent this essentially organizational concern and also that this matter was not a source of controversy among the classical jurists, for the question of general sovereignty does not arise ...